2019
DOI: 10.1021/acsami.8b20138
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis of Silicon Quantum Dots with Highly Efficient Full-Band UV Absorption and Their Applications in Antiyellowing and Resistance of Photodegradation

Abstract: UV absorbers are very effective in the fields of antiyellowing, resistance of photocatalytic degradation, and sunscreen cosmetics. However, commercialized UV absorbers have the drawbacks of toxicity, low absorption efficiency, transparency, etc. Here, we report for the first time silicon quantum dots as full-band UV absorbers. The NH-refunctionalized silicon quantum dots with high-performance UV absorption were successfully synthesized under the synergistic effect of sodium citrate and ethanediamine, and the (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 52 publications
0
28
0
Order By: Relevance
“…SiCDs show preeminent advantages transcending common nanomaterials in building solid-state transparent devices. Other [60] Copyright 2019, American Chemical Society. b) Nonlinear performances of CDs, SiCDs, and SiCDs gel glasses under excitation of 532 nm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SiCDs show preeminent advantages transcending common nanomaterials in building solid-state transparent devices. Other [60] Copyright 2019, American Chemical Society. b) Nonlinear performances of CDs, SiCDs, and SiCDs gel glasses under excitation of 532 nm.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, their optical properties was long-term stable even after 20 months, superior to conventional organic or inorganic UV absorbers. Hu et al [60] put forward that -OH is beneficial for SiCDs to achieve full-band UV absorption. As the concentration increases, zeta potential results showed that the repulsion between functionalized SiCDs would increase, leading to better dispersibility.…”
Section: Sicds In Optical Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly used stabilizers for polymer materials include ultraviolet absorbers (UVA) [7], HALS (hindered amine light stabilizer) [8], and light shielding agents [9]. For the conservation of cultural relics, UVA is typically used to reduce the aging of protective materials [10].…”
Section: Wpływ Aminowego Stabilizatora śWiatła Z Zawadą Przestrzenną Na Starzenie Utwardzanego Wilgocią Poliuretanu Stosowanego Jako Konsmentioning
confidence: 99%
“…Due to the quantum confinement effect [1,2], quantum dots are of great interest in applications of light and electricity [3,4,5]. In particular, luminescent silicon quantum dots (SiQDs), as representative zero-dimensional silicon nanostructures, are promising for solar cells [6], light emitting diodes [7], photocatalytic degradation [8], bio-imaging [9] and fluorescent probes [10] with low cytotoxicity [11], excellent water dispersibility [12], favorable biocompatibility [13], surface modification [11,14] and so on. Although, preparation methods of SiQDs have been extensively explored with electrochemical etching silicon wafers using HF [15], reduction of hydrogen silsesquioxane by H 2 at high temperature [16], laser pyrolysis of silanes [17], microwave assisted method for reducing silane coupling agent by sodium citrate [18], gas phase reduction method for reducing SiO 2 gel by H 2 or Mg vapor [19], liquid phase reduction silane method for lithium aluminum hydride reduction halosilane [20], high energy grinding ball method based on silicon wafer [21] and so on, these synthetic methods possess complicated procedures, hazardous reagents (HF, H 2 , H 2 SO 4 , SiX 4 ), complex morphology, low purity, uneven size and highly demanding equipment.…”
Section: Introductionmentioning
confidence: 99%